O10.1. CORRELATIONS BETWEEN INSULIN RESISTANCE AND PERIPHERAL IMMUNITY IN FIRST-EPISODE PSYCHOSIS – A GENE EXPRESSION STUDY. (9th April 2019) - Mantere, Outi; Honkanen, Jarno; Trontti, Kalevi; Hovatta, Iiris; Keinanen, Jaakko; Vaarala, Outi; Suvisaari, Jaana
Abstract: Background: The changes in glucose metabolism and triglycerids are the most consistently reported peripheral findings in the early phase of first-episode psychosis (FEP). Here, we aim at understanding the correlations between insulin resistance and peripheral immunity in FEP. Methods: We recruited patients with FEP (n=67) and matched controls (n=38), aged 18–40 years. Fasting peripheral blood samples were collected between 8 and 10 a.m. in 10ml PAXgene tubes. We applied the NanoString nCounter in-solution hybridization technology to determine gene expression levels of 186 candidate genes reflecting activation of the immune system or associated with metabolic changes during anti-psychotics. We present correlations of expression levels with insulin resistance, endogenous insulin secretion (connecting (C)-peptide) and lipids in patients and controls. Results: Initially, the patients as compared to controls had a higher HOMA index (1.7 vs 1.1, p=0.003) and triglycerids (1.11 vs 0.79, p=0.003) and lower levels of HDL (1.36 vs 1.47, p=0.004), reflecting insulin resistance. In patients, markers of the peripheral immune response robustly correlated with higher fasting glucose, HOMA index and triglycerids, and lower HDL. Discussion: An activation of the peripheral immune system in FEP patients correlated with an abnormal glucose and lipid metabolism. While cardiovascular diseases and cancer are the reasons for excess mortality in psychosis, this novel knowledge could help in targeted add-on treatments to prevent the unfavorable course towards physical complications.